Kegiatan Kesenian dan Penyuluhan Informasi Terkait MCK di Sungai di Desa Pandowan - pudyatmoko, yohanes sri (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Pandowan Village is one of the most populous villages located in Galur District, Kulon Progo, Yogyakarta. This village is a village that has various potentials ranging from nature, society to very interesting arts. This is evidenced by the existence of 8 art activities that are divided into each village, and the event of Reog Pandu Budaya (Ramayana Story) was held in this Pandowan Village. In addition, Pandowan Village also has extensive agricultural land and is fed by rivers for irrigation of the rice fields, however, the existence of parties carrying out MCK in the river will eventually pollute the river and of course have a bad impact on the health of the community around Pandowan Village. Thus, the writing of this KKN Journal Papers discusses these 2 topics. The data collection method used is literature study and the data collection process is through websites, journals, previous reports and carried out online. Our observations show that Pandowan Village has a lot of excellent potential and deserves to be developed. KKN is a place for students to develop their competencies and as a place to contribute to the surrounding community.